Anaesthesia and airway management in mucopolysaccharidosis. Issue 2 (30th November 2012) - Walker, Robert; Belani, Kumar G.; Braunlin, Elizabeth A.; Bruce, Iain A.; Hack, Henrik; Harmatz, Paul R.; Jones, Simon; Rowe, Richard; Solanki, Guirish A.; Valdemarsson, Barbara
Abstract: This paper provides a detailed overview and discussion of anaesthesia in patients with mucopolysaccharidosis (MPS), the evaluation of risk factors in these patients and their anaesthetic management, including emergency airway issues. MPS represents a group of rare lysosomal storage disorders associated with an array of clinical manifestations. The high prevalence of airway obstruction and restrictive pulmonary disease in combination with cardiovascular manifestations poses a high anaesthetic risk to these patients. Typical anaesthetic problems include airway obstruction after induction or extubation, intubation difficulties or failure [can't intubate, can't ventilate (CICV)], possible emergency tracheostomy and cardiovascular and cervical spine issues. Because of the high anaesthetic risk, the benefits of a procedure in patients with MPS should always be balanced against the associated risks. Therefore, careful evaluation of anaesthetic risk factors should be made before the procedure, involving evaluation of airways and cardiorespiratory and cervical spine problems. In addition, information on the specific type of MPS, prior history of anaesthesia, presence of cervical instability and range of motion of the temporomandibular joint are important and may be pivotal to prevent complications during anaesthesia. Knowledge of these risk factors allows the anaesthetist to anticipate potential problems that may arise during or after the procedure. Anaesthesia in MPS patients should be preferably done by an experienced (paediatric) anaesthetist, supported by a multidisciplinary team (ear, nose, throat surgeon and intensive care team), with access to all necessary equipment and support.